2018
DOI: 10.1080/07481187.2018.1504836
|View full text |Cite
|
Sign up to set email alerts
|

Examining the transitions between living and dying roles at end-of-life

Abstract: Improvements in the diagnosis and disclosure of dying mean that nowadays dying people typically live with an awareness of their status for longer than they have previously.However, little is known regarding how transitions between living and dying roles occur during this time. In this grounded theory study, we investigated role transitions at end-of-life.We found that dying people periodically foreground and background living and dying selfhoods, focus on living day-by-day and goal-by-goal and reframe dying ro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 30 publications
(32 reference statements)
0
6
0
Order By: Relevance
“…Taken collectively, our findings highlight the potential for confusion and misalignment in end-of-life role relations, resulting from a lack of clarity and associated uncertainty regarding role expectations at any given time. Recent research has indicated that the contemporary drama of dying often plays out over a longer timeframe than in historical times and, in response to this, dying persons periodically transition into and out of the living and dying selfhood (Breen, Aoun, O'Connor, Howting, & Halkett, 2018;Kellehear, 2009;Lowrie et al, 2018). Our research suggests that, to some extent, contemporary social scripts to guide dying role relations have not yet evolved to reflect this longer and more variable drama of dying.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…Taken collectively, our findings highlight the potential for confusion and misalignment in end-of-life role relations, resulting from a lack of clarity and associated uncertainty regarding role expectations at any given time. Recent research has indicated that the contemporary drama of dying often plays out over a longer timeframe than in historical times and, in response to this, dying persons periodically transition into and out of the living and dying selfhood (Breen, Aoun, O'Connor, Howting, & Halkett, 2018;Kellehear, 2009;Lowrie et al, 2018). Our research suggests that, to some extent, contemporary social scripts to guide dying role relations have not yet evolved to reflect this longer and more variable drama of dying.…”
Section: Discussionmentioning
confidence: 81%
“…The findings outlined here relate specifically to one of the categories from the overarching study, namely "alignment and mismatch in role relations". For other published components of the study, readers are directed to Lowrie, Ray, Plummer, and Yau (2018).…”
Section: Methodsmentioning
confidence: 99%
“…Terminal illness bloggers seem to exist in a liminal state between life and death, related to the process of foregrounding and backgrounding life and death noted by Lowrie et al (2019), which gives them license to claim a special spiritual status. For example, Sophie calls herself "the cancer whisperer," which suggests that like "horse-whisperers" who have a special bond and power to control wayward horses, she has a special bond with others faced with a terminal diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…This resonates with the existential ambivalence identified by Flaherty (2018) in her analysis of one woman's transitory process following a terminal diagnosis which involved a focus on both dying and living well. Others have also noted how people approaching the end-of-life periodically foreground and background living and dying selfhoods (Lowrie et al, 2019). Wakefield et al (2018) conducted a systematic review of patient empowerment among those with a life limiting illness at an advanced stage.…”
Section: Introductionmentioning
confidence: 99%
“…In the context of patient EOL, the roles and boundaries of the patient-provider relationship become opaque and porous (Lowrie et al, 2019). The traditional therapeutic alliance becomes less accessible.…”
Section: Introductionmentioning
confidence: 99%